Sabbatical leave report: sabbatical Fall 2013 - Volkman, Richard (2013)
This sabbatical leave was devoted to revising and editing material for a book project with the working title, Meditations on Heroic Individualism. The principle objective was to have a finished manuscript, ready for submission to publishers. Additionally, a proposal was developed to add Special Topics course, Ethical Individualism, as a permanent course.
Keywords: dept.phi; faculty_collection; sabbatical_report

The making of modern Turkey: nation and state in eastern Anatolia, 1913–1950 - Marsoobian, Armen T (Journal of Genocide Research, 2013)
1 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/123-399-132-760-077 tex.type: [object Object]
Keywords: dept.phi

Collective intelligence and ethical individualism - Volkman, Richard (ACM Sigcas Computers and Society, 2013)
0 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/113-594-448-693-14X tex.type: [object Object]
Keywords: dept.phi